If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + -37) + -8 = -36 Reorder the terms: -7(-37 + x) + -8 = -36 (-37 * -7 + x * -7) + -8 = -36 (259 + -7x) + -8 = -36 Reorder the terms: 259 + -8 + -7x = -36 Combine like terms: 259 + -8 = 251 251 + -7x = -36 Solving 251 + -7x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-251' to each side of the equation. 251 + -251 + -7x = -36 + -251 Combine like terms: 251 + -251 = 0 0 + -7x = -36 + -251 -7x = -36 + -251 Combine like terms: -36 + -251 = -287 -7x = -287 Divide each side by '-7'. x = 41 Simplifying x = 41
| 2x^2+6xy-9y^2=x+2y | | -63+3x=7x+21 | | 3p^2=3p | | 3(4z-2x)= | | 4x=7x-33 | | 3(x+13)+4=-23 | | 7x-55=x+35 | | -10(x+33)+-8=-28 | | b+6=-2b+1 | | S*6-39=27 | | 33=3+5y | | X+10=14-x | | 2x^2+29=10x+x^2 | | 3+9y=66 | | 4x^2-5x-6.01=0 | | 100+100=h | | 10x+4-2x=14-4x+6+8x | | 3n-10=0 | | 3x-y=3d | | 8+(n+9)=21 | | Y=2x^3-14x^2+24x | | 4e+9=-63-8e | | 4(w-3)-2=-4(-6w+6)-8w | | (3n-5)(n-6)=0 | | 63-2e=14-9e | | 5-x=10x | | 33=6+3h | | 4e+6=-50-4e | | 5x+3y=182 | | 8+3e=6+e | | 6a+2=7a-1 | | 3e-2=13e-62 |